Reducing the CP content in broiler feeds: impact on animal performance, meat quality and nitrogen utilization. (2nd May 2017) - Belloir, P.; Méda, B.; Lambert, W.; Corrent, E.; Juin, H.; Lessire, M.; Tesseraud, S.
Abstract : Reducing the dietary CP content is an efficient way to limit nitrogen excretion in broilers but, as reported in the literature, it often reduces performance, probably because of an inadequate provision in amino acids (AA). The aim of this study was to investigate the effect of decreasing the CP content in the diet on animal performance, meat quality and nitrogen utilization in growing-finishing broilers using an optimized dietary AA profile based on the ideal protein concept. Two experiments (1 and 2) were performed using 1-day-old PM3 Ross male broilers (1520 and 912 for experiments 1 and 2, respectively) using the minimum AA:Lys ratios proposed by Mack et al . with modifications for Thr and Arg. The digestible Thr (dThr): dLys ratio was increased from 63% to 68% and the dArg:dLys ratio was decreased from 112% to 108%. In experiment 1, the reduction of dietary CP from 19% to 15% (five treatments) did not alter feed intake or BW, but the feed conversion ratio was increased for the 16% and 15% CP diets (+2.4% and +3.6%, respectively), while in experiment 2 (three treatments: 19%, 17.5% and 16% CP) there was no effect of dietary CP on performance. In both experiments, dietary CP content did not affect breast meat yield. However, abdominal fat content (expressed as a percentage of BW) was increased by the decrease in CP content (up to +0.5 and +0.2 percentage point, in experiments 1 and 2, respectively). In experiment 2, meat quality traits responded to dietary CP content with a higher ultimate pH and lower lightness and drip loss values for the low CP diets. Nitrogen retention efficiency increased when reducing CP content in both experiments (+3.5 points/CP percentage point). The main consequence of this higher efficiency was a decrease in nitrogen excretion (−2.5 g N/kg BW gain) and volatilization (expressed as a percentage of excretion: −5 points/CP percentage point). In conclusion, this study demonstrates that with an adapted AA profile, it is possible to reduce dietary CP content to at least 17% in growing-finishing male broilers, without altering animal performance and meat quality. Such a feeding strategy could therefore help improving the sustainability of broiler production as it is an efficient way to reduce environmental burden associated with nitrogen excretion.